The higher federal court original specialty in dissolve the conflict of jurisdiction - شبر رافع خضر; حسن منتهى فزاع (Journal of Legal Sciences, 2019)
The Supreme Federal Court of Iraq was established by the Federal Supreme Court Law No. (30) For the year 2005 on the basis of the provisions of the Iraqi State Administration Law for the transitional period of 2004. The law included a clear reference to the main purpose for which the Federal Supreme Court was established, the separation of jurisdictions between different levels of government, as well as its competence to control the constitutionality of laws. It was also referred to in the Constitution of 2005 and defined its powers in Article (93) of it, in addition to the other terms of reference in the other articles of the Constitution and the laws in force, and from reading the texts of the above Constitution, the Federal Supreme Court can become an institution with power and is expected to be referred We have examined the jurisdiction of the Federal Supreme Court to resolve the conflict of jurisdiction in the light of the provisions of the Constitution of the Republic of Iraq for 2005 in three sections preceded by a preliminary study divided as follows: The first part deals with the original or (direct) jurisdiction of the Federal Supreme Court in resolving the conflict of jurisdiction between different levels of government. The second section deals with the inherent or direct jurisdiction of the Federal Supreme Court in resolving the conflict of jurisdiction. The third topic is devoted to the jurisdiction of the Federal Supreme Court in resolving the conflict of jurisdiction between the governor and the provincial council or the local council under the law of governorates not organized in the region No. 21 of 2008 amended. And then concluded it all with a conclusion, which showed the most prominent findings and conclusions of the recommendations, and the most important findings of the following :- First: The Federal Supreme Court is competent to adjudicate the conflict of jurisdiction in a genuine and direct manner under the Constitution, through its competence contained in the text of Article 93 (Paragraphs IV, V, VIII , A and B).The Law of Governorates not organized in Region No. 21 of 2008, Resolve the conflict of jurisdiction between the governor and the provincial council or the local council Second: The Federal Supreme Court is still operating under its old law, which was enacted under the Transitional Administrative Law, which is considered unconstitutional and is characterized by a lot of shortcomings and lack of detail in its provisions and incompatibility between the jurisdictions of the court contained therein with the competence under the 2005 Constitution. The most important recommendations are: First: to expedite the issuance of the Federal Supreme Court Act in the form that ensures its issuance in accordance with the Constitution of the Republic of Iraq for the year 2005, and recommend the legislator as follows: • With regard to the process of nomination and selection of members of the Federal Supreme Court, there should be a role for regions and governorates not organized in the province, The role of the Council of the Union in the process of ratification of the selection of members of the Court, and here another lawsuit to the legislator the need to accelerate the adoption of the law of the Council of the Union and its composition. • Calling on the Iraqi legislator to find specific criteria in what is considered a legislative decision that the Federal Supreme Court is competent to consider and what is considered an administrative decision that falls within the jurisdiction of the administrative judiciary, in order to prevent overlap of jurisdiction while preventing conflicting decisions from both sides due to conflict of jurisdiction Second: we find that many of the cases have been rejected by the court for lack of jurisdiction, and here is an invitation to the Federal Supreme Court to invest any opportunity through the legal challenge that is presented to them in the conflict of jurisdiction for the purpose of finding solutions that are consistent with the Constitution on controversial topics and failed to resolve other authorities In order to preserve the unity of the state and its federal system